Implementing an Islamic Religious Education Model to Foster Students' Religious Moderation Character: A Case Study at SDN 01 Lebakharjo - Aisyah Nindi Antika; Muhammad Husni (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
Religious moderation has become an essential objective of character education in multicultural societies, requiring educational approaches that integrate religious understanding with inclusive values and everyday practice. This study explores how an Islamic Religious Education (IRE) model is implemented to foster students' religious moderation character at SDN 01 Lebakharjo, Indonesia. A qualitative descriptive case study was employed, involving school principals, Islamic Religious Education teachers, classroom teachers, and students selected through purposive sampling. Data were collected through classroom observations, semi-structured interviews, and document analysis, and were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that religious moderation is cultivated through an interconnected educational process combining classroom instruction, religious habituation, teacher role modelling, extracurricular activities, and a supportive school culture. These practices encourage students to develop tolerance, mutual respect, responsibility, cooperation, and social awareness as integral aspects of their daily behaviour. The implementation is strengthened by collaborative leadership, teacher commitment, and parental involvement, although challenges remain due to digital media influence, family background differences, and diverse student characteristics. This study contributes to the literature by presenting religious moderation as the outcome of a holistic educational ecosystem rather than isolated instructional activities. The findings also provide practical insights for educators and policymakers seeking to strengthen character education through contextually grounded Islamic Religious Education practices